The pulse of liability of foreignness: dynamic legitimacy and experiences effects in the German car market - Ulrich Kaiser; Wolfgang Sofka (Zentrum für Europäische Wirtschaftsforschung (ZEW), 2006)
Globalization has provided many companies with new opportunities for growth and efficiency. This requires them to operate successfully across cultural and social borders. These can be stumbling blocks to internationalization and have been found to cause frequent errors and delays for multinational companies. Such liabilities of foreignness are persistent in nature. We investigate the causes behind these detrimental effects. We identify two major factors conceptually: a lack of legitimacy in the host country on the demand side and a lack of responsiveness on the side of the multinational corporation. We test these hypotheses empirically using a comprehensive sample of the German car market, which is especially suitable due to its established domestic producers and international competitors. Our results suggest that the two factors interact. For less experienced customer groups, we find that legitimacy is the dominant factor behind the effects of liability of foreignness. As customer experience increases, liability of foreignness caused by a lack of responsiveness becomes more of an issue.
Keywords: M10; L62; F23; 330; Liability of foreignness; internationalization strategy; globalization